ANALYSIS ON THE IMPLEMENTATION OF POLICY FOR THE NON-JUDICIAL SETTLEMENT OF PAST GROSS VIOLATIONS OF HUMAN RIGHTS IN INDONESIA - Muhammad Iqbal; Ima Mayasari (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study analyzes the implementation of the non-judicial resolution policy for past gross human rights violations utilizing Merilee S. Grindle's (1980) Policy Implementation Theory, examining two primary dimensions: the content of policy and the context of implementation. The findings reveal that the policy's implementation continues to encounter significant obstacles. These challenges are primarily driven by a lack of legal legitimacy, as the policy is merely grounded in Presidential Decree Number 17 of 2022 concerning the Establishment of the Team for the Non-Judicial Resolution of Past Gross Human Rights Violations. Furthermore, there is a distinct disharmony between this legal basis and existing statutory regulations governing the resolution of past gross human rights violations. The implementation is also hindered by the minimal involvement of victims and their families in both the formulation and execution of the policy, as well as a perceptible lack of political will from the current administration to sustain its implementation. Consequently, several key recommendations are proposed: the state must redraft a robust legal framework to resolve gross human rights violations through non-judicial mechanisms via a Truth and Reconciliation Commission (TRC); the state should issue a formal apology to the victims and their families; and the government must establish clear delineations of authority among state institutions tasked with human rights functions. These measures are imperative to achieve national reconciliation in alignment with the paradigm of Transitional Justice, which inherently encompasses truth-seeking, the prosecution of perpetrators, the restoration of victims' rights, and guarantees of non-recurrence.